PENGALAMAN ORANG TUA MERAWAT ANAK DENGAN EPILEPSI - Maria Octavia Liswanti Vitaningtyas (NHM PRESS, 2022)
PARENTS' EXPERIENCE OF CARING FOR CHILDREN WITH EPILEPSY IN JAKARTA AND SURROUNDINGS IN 2021 Maria Octavia Liswanti Vitaningtyas STIK Sint Carolus Undergraduate Nursing Study Program ABSTRACT Parents of children with epilepsy will face various challenges in caring for their children. Epilepsy treatment takes a long time that will cause various problems for parents and which can affect children’s quality of life. This study aims to explore more deeply the parents’ experience of caring for children with epilepsy. This study used a descriptive phenomenology design, with 13 participants and an age range of 27 to 44. Data collection was taken in December 2020-February 2021 by an in-depth interview. The analysis technique used the Colaizzi technique. This study resulted in five themes: the parental adaptability to epilepsy, changes in parental life, readiness for handling epilepsy, parental coping mechanisms, and parental expectations. Nurses should increase knowledge when providing education to parents of children with epilepsy so that parents can increase their understanding of the handling and treatment of epilepsy. keywords: children, epilepsy, experience, treat